ผลการฝึกด้วยเครื่องเกม Wii-hab ต่อการฟื้นกำลังกล้ามเนื้อ และการทำงานของแขนในผู้ป่วยโรคหลอดเลือดสมองกึ่ง เฉียบพลัน: การศึกษานำร่องแบบสุ่มและมีกลุ่มควบคุม - ปราชญ์พยนต์, ประภาภรณ์; ธีรเนตร, ไกรวัชร (ASEAN Journal of Rehabilitation Medicine, 2015)
Effects of Wii-hab Training on Motor Recovery and Motor Function of Upper Extremity in Subacute Stroke Patients: a Pilot Randomized Controlled Trial Prachpayont P, Teeranet G Department of Physical Medicine and Rehabilitation, Phramongkutklao Hospital Objectives: To evaluate the effectiveness of Wii-Hab training on motor recovery and motor functions of upper extremity in stroke patients. Study Design: a pilot randomized controlled trial and assessor-blinded. Setting: Physical Medicine and Rehabilitation Department, Phramongkutklao Hospital Subjects: Hemiplegic stroke patients within 6 months after onset Methods: Patients were randomly assigned to either a Wii-hab group (n=10) or a control group (n=10). Both groups participated in a conventional stroke rehabilitation program, 5 days a week, for 4 weeks. The Wii-hab group received an additional 30 minutes of Wii-hab training program of shoulder flexion, abduction, internal-external rotation, elbow flexion-extension, forearm supination-pronation, wrist flexion-extension and finger flexion movements. Main Outcome Measures: Brunnstrom stages of motor recovery, modified Ashworth Scale (MAS) for spasticity and motor assessment scale for upper extremity-related functions were assessed at pre-intervention (week 0), during intervention (week 2), after completion of intervention (week 4) and at follow-up visit (week 8). Results: A total of 20 patients with stroke, 13 males and 7 females with mean age of 57.3 (SD 11) years old and mean time of onset 59.9 (SD 35) days, were recruited into the study. There were no significantly differences of demographic data between two groups. The Brunnstrom stages for upper extremity recovery and the motor assessment scales showed more significant improvements in the Wii-hab group than in the control group at the end of week 4 (p<0.05). No significant differences in upper extremity MAS between the two groups at the end of week 4 and at the follow-up visit of week 8. Conclusions: Wii-hab training in conjunction with conventional stroke rehabilitation program enhances motor recovery and motor functions of upper extremity in subacute stroke patients as compared to conventional rehabilitation program. บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาผลการฝึกฝนโดยใช้เกม Wii-hab ในการฟื้นฟูกำลังกล้ามเนื้อและความสามารถในการทำงานของแขนและมือในผู้ป่วยโรคหลอดเลือดสมองระยะกึ่งเฉียบพลัน รูปแบบการวิจัย: การศึกษาวิจัยนำร่องแบบสุ่มและมีกลุ่มควบคุม สถานที่ทำวิจัย: กองเวชศาสตร์ฟื้นฟู โรงพยาบาลพระมงกุฎ-เกล้า กลุ่มประชากร: ผู้ป่วยโรคหลอดเลือดสมองที่อ่อนแรงครึ่งซีก ซึ่งมีระยะเวลาหลังเกิดโรคไม่เกิน 6 เดือน วิธีการศึกษา: แบ่งผู้เข้าร่วมวิจัยเป็น 2 กลุ่ม (กลุ่มละ 10 คน) ทั้งกลุ่มทดลองและกลุ่มควบคุมได้รับการฟื้นฟูแบบมาตรฐาน 5 วันต่อสัปดาห์ ติดต่อกัน 4 สัปดาห์ แต่กลุ่มทดลองได้ฝึกกำลังกล้ามเนื้อการทำงานของแขนและมือด้วยเกม Wii-hab เป็นเวลา 3 วันต่อสัปดาห์ ครั้งละ 30 นาที ที่ประกอบด้วยการเคลื่อนไหวข้อไหล่ ศอก ข้อมือและมือข้างที่อ่อนแรง ประเมินผล การฟื้นกำลังกล้ามเนื้อแขนโดยใช้ Brunnstrom stage, แบบประเมินความตึงตัวของกล้ามเนื้อโดย modified Ashworth scale (MAS)) และความสามารถใช้แขนและมือทำกิจกรรมโดย motor assessment scale ฉบับภาษาไทย) ที่ก่อนฝึก(สัปดาห์ที่ 0) ขณะฝึก (สัปดาห์ที่ 2) หลังฝึกเสร็จทันที (สัปดาห์ที่ 4) และสัปดาห์ที่ 8 นับจากการประเมินครั้งแรก ผลการศึกษา: ผู้เข้าร่วมวิจัย 20 ราย เป็นชาย 13 คน หญิง 7 คน อายุเฉลี่ย 57.3 (ส่วนเบี่ยงเบนมาตรฐาน 11) ปี ระยะเวลาหลังเกิดโรคหลอดเลือดสมองเฉลี่ย 59.95 (ส่วนเบี่ยงเบนมาตรฐาน 35) วัน และไม่มีความแตกต่างกันระหว่างข้อมูลพื้นฐานของทั้งสองกลุ่ม เมื่อเปรียบเทียบกลุ่มทดลองและกลุ่มควบคุมหลังการฝึกที่สัปดาห์ที่ 4 พบว่ากลุ่มทดลองม Brunnstrom stage ของแขน และความสามารถในการใช้แขนและมือทำกิจกรรม มากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติ (p<0.05) โดยไม่มีผลต่อเนื่องถึงสัปดาห์ที่ 8 และไม่มีผลต่อความตึงตัวของกล้ามเนื้อในทั้งสองกลุ่ม สรุป: การฝึกด้วยเกม Wii-hab ร่วมกับการฟื้นฟูแบบมาตรฐานเป็นเวลา 4 สัปดาห์ ช่วยเพิ่มกำลังกล้ามเนื้อและความสามารถในการทำงานของแขนในผู้ป่วยโรคหลอดเลือดสมองระยะกึ่งเฉียบพลัน มากกว่าการฟื้นฟูแบบมาตรฐานเพียงอย่างเดียว